Skin-to-Skin Care and the Development of the Preterm Infant Oral Microbiome - Hendricks-Muñoz, Karen D.; Xu, Jie; Parikh, Hardik I.; Xu, Ping; Fettweis, Jennifer M.; Kim, Yang; Louie, Moi; Buck, Gregory A.; Thacker, Leroy R.; Sheth, Nihar U. (American Journal of Perinatology, 2015)
Objective The oral cavity represents an initial entry way for oral and gut indigenous colonization. Skin-to-skin (STS) care, in which the mother holds the diaper clad naked preterm (PT) infant between her breasts, is associated with improved digestive function, decreased stress, and improved survival. This study evaluated the development of oral microbial colonization repertoires and health characteristics in PT infants with or without STS exposure.Methods Saliva from 42 PT infants (<32 weeks of gestation at birth) was collected prospectively at 1 month and/or at discharge. High-throughput 16S rRNA sequencing identified microbial diversity and prevalence of bacterial signatures correlated with clinical STS or non-STS care.Results Corrected for gestational age (CGA) at sampling, bacterial taxa demonstrated increased Streptococcus as a signature of oral repertoire maturation. STS was associated with increased Streptococcus (p < 0.024), while non-STS was associated with greater Corynebacterium (p < 0.023) and Pseudomonas (p < 0.019) in infants ≤ 32 weeks CGA. In infants > 32 weeks CGA, Neisseria and Acinetobacter were more prevalent, 50 vs. 16.7% and 40 vs. 0%, respectively. STS care was associated with shorter hospitalization (p < 0.039).Conclusion STS care during earlier gestation was associated with a distinct microbial pattern and an accelerated pace of oral microbial repertoire maturity.
Keywords: skin to skin; preterm infant; oral microbiome